Humanismo para el cambio: el caso de la Sede de Occidente, Universidad de Costa Rica. - Araya, Mauricio (My University, 2019)
The current paradigm of individual success, driven by ambition and greed, generates the overexploitation of people and natural resources among the population mass. In this situation, humanism is the approach that will produce social transformation, and therefore, the implementation of educational processes that foster a more humane, comprehensive, and inclusive culture is required. In Costa Rica’s western region, the University of Costa Rica, located in the San Ramon central county, provides mediation between culture and humanistic knowledge, with the participation, every six months, of approximately one thousand six hundred students from communities far removed from the capital city. Humanities and General Studies courses must be developed with stimulating and innovative teaching strategies with the goal of generating a cultural and educational revolution that promotes critical thinking and fosters virtues and values to counteract negative self-destructive attitudes, rooted in the globalized culture. In order to account for such a reality, the Humanities and General Studies courses offered at the Western Campus of the University of Costa Rica will be approached as a case study to build academic efforts that will impact both political and community spheres.
El paradigma actual de éxito individual, impulsado por la ambición y la avaricia de quienes controlan la economía mundial genera una sobreexplotación de personas y recursos naturales. Ante esta situación, el humanismo es el enfoque que producirá una transformación social, y por eso se requiere la implementación de procesos educativos que fomenten una cultura más humana, integral e incluyente. En la Sede de Occidente de la Universidad de Costa Rica, ubicada en el cantón central de San Ramón se da una mediación entre cultura y conocimiento humanístico, donde semestralmente participan cerca de mil seiscientos estudiantes provenientes de comunidades periféricas en su mayoría rurales. Los cursos de Humanidades y Estudios Generales se deben desarrollar con estrategias didácticas estimulantes e innovadoras, cuya meta está en generar una revolución cultural y educativa que propicie el pensamiento crítico, fomente valores y virtudes, en contrapeso con las nefastas actitudes autodestructivas, arraigadas en la cultura globalizada. Para reflejar dicha realidad se tomará como estudio de caso los cursos de Humanidades y Estudios Generales que se imparten en la Sede de Occidente, con el fin de constituir un esfuerzo académico que logre impactar también en los ámbitos políticos y comunales.
Keywords: HUMANISMO; CULTURA; GLOBALIZACIÓN; MEDIACIÓN PEDAGÓGICA